DAMPAK NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM YANG DIMODERASI OLEH PERTAMBAHAN KASUS COVID 19 DI INDONESIA - Hayu Wikan Kinasih; Rizza Hardiyanti Rukmana (Universitas Muhammadiyah Malang, 2021)
The existence of Covid-19 which began to spread throughout the region in the world resulted in economic paralysis in various countries. This study aims to examine the effect of the rupiah exchange rate on stock prices, which is moderated by the number of positive cases of Covid-19 in Indonesia. This study took a sample of the hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange because the companies of this sector is heavily affected by the covid-19 pandemic. This research was conducted over a period of 4 months, from March 2020 to June 2020. The sampling period was based on determining the status of the Covid-19 pandemic in Indonesia in March 2020 which resulted in many companies in this sub-sector experiencing shocks. This study uses a moderated regression analysis method. The results prove that Rupiah Exchange Rate affects the Stock Price of the Hotel, Restaurant and Tourism sub-sector. In addition, the increase in Covid-19 cases also moderated the relationship between the rupiah exchange rate and the stock price.